Exposure to Any Antenatal Corticosteroids and Outcomes in Preterm Infants by Gestational Age: Prospective Cohort Study. Issue 4 (December 2017) - Travers, Colm P.; Clark, Reese H.; Spitzer, Alan R.; Das, Abhik; Garite, Thomas J.; Carl, Waldemar A.
Abstract : ( BMJ . 2017;356:j1039) The use of antenatal corticosteroids is recommended for women at risk of preterm delivery beginning at 24 weeks gestation and potentially at 23 weeks gestation. However, there are limited data to support this recommendation at the youngest end of this gestational age range. This prospective cohort study was undertaken, therefore, to investigate the effect of exposure to antenatal corticosteroids on neonatal outcomes as a function of gestational age.